Covid-19 Impact and Recovery: Online and Offline Marketing Strategy For Victory Building Materials Store - Stella Wijaya; Aprihatiningrum Hidayati (Business Review and Case Studies, 2024)
The Covid-19 pandemic significantly disrupted various sectors in the third quarter of 2020, notably the construction sector, an essential contributor to Indonesia's Gross Domestic Product (GDP) growth. Located in Glodok, one of Jakarta's most populous and commercially active regions, the Victory Building Materials Store exemplified this disruption. Experiencing a sharp 38.62% decline in sales revenue in 2020, the store grappled with intense marketing competition and the sweeping changes brought about by technological advancements. This study aimed to recommend an integrated online and offline marketing strategy tailored to this specific context. The research was qualitative, classified under conclusive descriptive research, employed interviews, FGDs, and document analysis. External analyses capturing the macro environment, industry dynamics, and customer behavior were conducted, while internal evaluations centered on Victory's existing marketing tactics. The results provided insights into market attractiveness, competitive positioning, and Victory Store's SWOT informed our strategy formulation. By enhancing segmentation, targeting, and positioning, with a keen focus on online sales, we aimed to elevate buyer brand awareness. The designed marketing mix strategy, encompassing the 7Ps, was projected to bolster the sales revenue of Victory Store until 2025. This study underscored the increasing significance of online sales channels, especially e-commerce platforms. Keywords: covid-19 impact, building materials store, e-commerce transformation, online marketing strategy, retail disruption